40. ASSOCIATED FACTORS RELATED WITH SOCIAL ANXIETY DISODER IN THE FRIST-YEAR STUDENTS AT THAI NGUYEN UNIVERSITY OF MEDICINE AND PHARMACY (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to determined the related factors of social anxiety disorder in the first-year students in Thai Nguyen University of Medicine and Pharmacy in 2023.Subject and methods: A cross-sectional study was conducted at 1019 first-year students in Thai Nguyen University of Medicine and Pharmacy from July to December 2023.Results: Some related factors to incidence of social anxiety disorder include: medicine (OR = 1.70; p < 0.05), only child in family (OR = 1.87; p < 0.05), self-deprecation (OR = 1.68; p < 0.05), time to use social network greater than or equal to 3 hours per day (OR = 1.49; p < 0.05), having difficult to find another friend (OR = 2.07; p < 0.05).Conclusion: Need for plans to advise, educate, and support first-year students to integrate into the new environment, reducing the incidence and increase of the disease.
Keywords: Social anxiety disoder; first-year student; related factors